Art Education online? MASP Educational Strategies in the Pandemic (Revista Apotheke, 2022)
This article makes reflections about educational strategies adopted by the São Paulo Museum of Art - MASP, during Pandemic, assuming that the Museum of Art, in its strength of meanings and possibilities, is the ideal place to work teaching and learning processes in Art. But how to do this during the pandemic? In social isolation, how can art education bring about changes for everyone? According to the proposal of the Apotheke magazine, we aim to problematize the reach of online strategies based on the museums educational actions, for which the Triangular Approach is the guide of our investigation and structures the analyzes we are carrying out. We will exemplify, with some texts (visual and textual) prepared by MASP audiences, contemporary social issues in dialogue with the museums collection, among which: the condition of women, sexism, racism and social inclusion. In short, we intend to consider the paths of Art Education in virtual teaching, as well as hybrid strategies and the urgent need to think and plan to democratize these practices.